A virtual reality social conditioned place preference paradigm for humans: Does trait social anxiety affect approach and avoidance of virtual agents? - Kiser, Dominik P.; Gromer, Daniel; Pauli, Paul; Hilger, Kirsten (Frontiers in Virtual Reality, 2022)
Approach and avoidance towards positive and negative social cues are fundamental to prevent isolation and to ensure survival. High trait social anxiety is characterized by avoidance of social situations and extensive avoidance is a known risk factor for the development of social anxiety disorder (SAD). Therefore, experimental methods to assess social avoidance behavior in humans are essential. As the Social Conditioned Place Preference (SCPP) paradigm is a well-established experimental paradigm in animal research to objectively investigate social approach-avoidance mechanisms, we retranslated this paradigm for human research using virtual reality. To this end, 58 healthy adults were exposed to either a happy- or angry-looking virtual agent in a specific room, and the effects of this encounter on dwell-time as well as evaluation of this room in a later test without an agent were examined. We did not observe a general SCPP effect on dwell time or ratings but revealed a moderation by trait social anxiety: Participants with higher trait social anxiety spent less time in the room in which the angry agent was present before, suggesting that higher levels of trait social anxiety foster conditioned social avoidance. However, further studies should replicate this observation and substantiate an association with social anxiety disorder. We discuss strengths, limitations, and technical implications of our paradigm for future investigations with the ultimate goal of gaining a comprehensive understanding of the mechanisms involved in social anxiety and to facilitate the development of new personalized treatment approaches by using virtual reality.